Epithet And Artistic Descriptions National Thought With Connection (English And Uzbek Stories In The Example Of) - Abdunabiyeva Bahroi Ikramjon kizi (International Journal Of Literature And Languages, 2025)
This article examines the relationship between epithets, artistic descriptions, and national mentality in English and Uzbek short stories from a comparative literary perspective. The study analyzes the role of epithets and descriptive techniques in the creation of literary imagery, the revelation of character traits, and the expression of psychological states and social context. Based on a comparative analysis of selected English and Uzbek short stories, the research highlights the close connection between artistic description, authorial style, national values, and cultural background. The findings demonstrate that epithets and artistic descriptions function as significant poetic mechanisms reflecting national mentality in literary texts. The article contributes to the theoretical and methodological development of comparative literary studies and stylistics.